ANALISIS PELAKSANAAN PERAN GENDER PADA ANGGOTA PUNGUAN BORSAK MANGATASI NABABAN DI KOTA PONTIANAK - Nababan, Ribka Mariani; Okianna, Okianna; Prancisca, Stella (Universitas Tanjungpura, 2024)
The aim of writing this thesis is to determine the implementation of